High-Pressure Synthesis and Study of NO+NO3− and NO2+NO3− Ionic Solids. (25th November 2008) - Kuznetsov, A. Yu.; Dubrovinsky, L.; Kurnosov, A.; Lucchese, M. M.; Crichton, W.; Achete, C. A.
Abstract : Nitrosonium-nitrateNO + NO 3 − and dinitrogen pentoxideNO 2 + NO 3 − ionic crystals were synthesized by laser heating of a condensed oxygen-richO 2 -N 2 mixture compressed to different pressures, up to 40 GPa, in a diamond anvil cell (DAC). High-pressure/high-temperature Raman and X-ray diffraction studies of synthesized samples disclosed a transformation ofNO + NO 3 − compound toNO 2 + NO 3 − crystal at temperatures above ambient and pressures below 9 GPa. High-pressure experiments revealed previously unreported bands in Raman spectra ofNO + NO 3 − andNO 2 + NO 3 − ionic crystals. Structural properties of both ionic compounds are analyzed. Obtained experimental results support a hypothesis of a rotational disorder ofNO + complexes inNO + NO 3 − and indicate a rotational disorder of ionic complexes inNO 2 + NO 3 − solid.